RANCANG BANGUN MADIA PEMBELAJARAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN DASAR DESAIN GRAFIS - Armiya Armiya; Asrul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Graphic Design is one of the required subjects of expertise package for Vocational students in Multimedia majors. These Graphic Design subjects are more directed at competency-based practicum which aims to equip students' skills in the field of graphic design so that students have strong skills with realistic theoretical foundations for students. Therefore there are still many students who do not understand the learning given by the teacher because the teacher has not used different techniques in delivering learning material, therefore it is necessary to design interactive learning media so that the teacher is easy to apply learning material and help students master the subject matter. In designing basic Graphic Design learning materials using explicit intruction models and through Interactive Multimedia learning procedures, starting from the needs analysis in designing, gathering data, identifying material to determining learning flow chart design, material collection or graphic needs. The interactive multimedi learning media is designed using the adobe director 11 application, and other applications such as Adobe Photoshop, Coreldraw, Camtasia as supporting applications so that it becomes an interactive multimedia learning media application that provides convenience for students in learning.Keywords: Learning Media, Interactive Multimedia, Graphic Design.